Dynamic Analysis of Hexagon Honeycomb Sandwich Plate Resting on Elastic Foundations - Minh Anh, Vu; Tung, Tran Thanh (VNU Journal of Science: Mathematics - Physics, 2024)
Dynamic analysis of hexagon honeycomb sandwich plate resting on elastic foundations are presented. Modeling is formed by 3 layers, in which core layer is hexagon honeyconb and facesheet layers is isotropic material. The Reddy’s first order shear deformation plate theory and Galerken method are used to investigate the influnce of elastic foundations, geometrical parameters and material properties of hexagon honeycomb on the  deflection – time curve. The value of the natural frequency was compared to the results reported in other works for evaluating the acuracy of used method.